Platelet participation in the pathogenesis of dermonecrosis induced by Loxosceles gaucho venom - Tavares, F. L. (2015)
Loxosceles gaucho spider venom induces in vitro platelet activation and marked thrombocytopenia in rabbits. Herein, we investigated the involvement of platelets in the development of the dermonecrosis induced by L. gaucho venom, using thrombocytopenic rabbits as a model. L. gaucho venom evoked a drop in platelet and neutrophil counts 4 h after venom injection. Ecchymotic areas at the site of venom inoculation were noticed as soon as 4 h in thrombocytopenic animals but not in animals with initial normal platelet counts. After 5 days, areas of scars in thrombocytopenic animals were also larger, evidencing the marked development of lesions in the condition of thrombocytopenia. Histologically, local hemorrhage, collagen fiber disorganization, and edema were more severe in thrombocytopenic animals. Leukocyte infiltration, predominantly due to polymorphonuclears, was observed in the presence or not of thrombocytopenia. Thrombus formation was demonstrated by immunohistochemistry at the microvasculature, and it occurred even under marked thrombocytopenia. Taken together, platelets have an important role in minimizing not only the hemorrhagic phenomena but also the inflammatory and wound-healing processes, suggesting that cutaneous loxoscelism may be aggravated under thrombocytopenic conditions.